(untitled) - McGraw, Eloise Jarvis (Boston, 1959)
Contents: craft and creativity; an idea hits you; plotting without pain; mainnikin or man; before you write - blueprint;...
Keywords: Fiction,Viễn tưởng; Technique,Kỹ thuật